2009
DOI: 10.1002/adfm.200900366
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of a Donor‐Acceptor Dyad Across Multiple Length Scales: Functional Architectures for Organic Electronics

Abstract: Molecular dyads based on polycyclic electron donor (D) and electron acceptor (A) units represent suitable building blocks for forming highly ordered, solution‐processable, nanosegregated D‐A domains for potential use in (opto)electronic applications. A new dyad, based on alkyl substituted hexa‐peri‐hexabenzocoronene (HBC) and perylene monoimide (PMI) separated by an ethinylene linker, is shown to have a high tendency to self‐assemble into ordered supramolecular arrangements at multiple length scales: macroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
127
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 82 publications
(124 reference statements)
0
127
0
Order By: Relevance
“…The white bars in Figure 9b are drawn for identifying the offset in the molecular packing. This peculiar molecular arrangement is surprising in view of the fact that 4-OC 17 BA does not show odd/even effect as already discussed in previous section. Thus, the odd/even difference that is insignificant in the monocomponent system appears to become prominent in the presence of the second component, which is the bipyridine unit in the present case.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The white bars in Figure 9b are drawn for identifying the offset in the molecular packing. This peculiar molecular arrangement is surprising in view of the fact that 4-OC 17 BA does not show odd/even effect as already discussed in previous section. Thus, the odd/even difference that is insignificant in the monocomponent system appears to become prominent in the presence of the second component, which is the bipyridine unit in the present case.…”
Section: Resultsmentioning
confidence: 63%
“…The location of kinks in this case is irregular. Having already seen that odd/even effects are quenched upon increasing the alkyl-chain length in the case of 4-OC 17 BA, we can speculate that 4-OC 11 BA can be a borderline case wherein the in- www.chemeurj.org terchain van der Waals interactions start becoming more significant than the odd/even difference. It must be noted at this juncture that 4-decyloxy as well as 4-dodecylA C H T U N G T R E N N U N G oxybenzoic acids show typical periodicity in the location of kinks along the lamella axis.…”
Section: Resultsmentioning
confidence: 95%
“…[1][2][3][4][5][6][7][8] Well-defined and reproducible nanoscale assemblies of donor-acceptor semiconducting materials are crucial for several devices in the optoelectronic applications. [1][2][3][4] From the perspective of device applications, it is highly desirable to translate the self-assembly of small molecules to processable polymers, which is a non-trivial task.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3d , 4 ] Such supramolecular architectures thus combine the ease of processing associated with solution methods along with the performance benefi ts of crystalline systems. Our group [ 5 ] and others have demonstrated that organic fi eld-effect transistors (OFETs) can be fabricated by dispersing arrays of supramolecular fi bers over source-drain electrode pairs.While band-like transport has been previously observed in high quality vapor-grown crystals, [ 6 ] hitherto, band-like transport in a solution-processed n-type system [ 7 ] has been elusive. Here we show that crystalline order, attainable through solution-based self-assembly, and specifi c molecular orientation, resulting in reduced dipolar disorder, lead to transport via delocalized carriers, and enhanced mobility.…”
mentioning
confidence: 99%